Pelatihan Penyusunan Karya Tulis Ilmiah Bagi Mahasiswa - Eman Sulaeman Nasim; Aida Fitriani; Jejen Jaenudin; Marzuki Marzuki; Sri Mulyeni (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2025)
The ability to write scientific papers is an essential competency for students in supporting academic achievement and readiness to face the world of work and research. However, many students still experience difficulties in compiling scientific papers, especially in the aspects of writing systematics, the use of academic language, and reference management. In response to this problem, the service team carried out a Scientific Writing Preparation Training for PASIM National University students as a form of implementation of the Tri Dharma of Higher Education in the aspect of community service. The training method uses an andragogy approach through interactive lectures, discussions, and hands-on practice. The activity was attended by around 50 students across study programs. The training material includes an introduction to scientific papers, writing rules, topic determination techniques, reference search and management, and outline preparation. Evaluation was carried out through observation, assessment of written products, and satisfaction questionnaires. The results showed an increase in participants' understanding by 30–40% based on the comparison of pre-test and post-test. All participants succeeded in compiling an outline of scientific papers, and the majority expressed satisfaction with the training. This activity has proven to be effective in improving students' scientific writing skills and fostering academic motivation and culture. It is recommended that similar training be carried out on an ongoing basis with intensive mentoring to support the improvement of the quality of human resources and contribution to student scientific publications.